Service Quality Of Room Attendant and Guest Satisfaction at The St. Regis Bali Resort - Ni Luh Apriliani Putri; I Gusti Made Wendri; I Nyoman Mei Rejeki (Politeknik Sahid, 2021)
The purpose of this study was to determine the quality of room attendant service to increase guest satisfaction at The St. Regis Bali Resort and to find out which indicators need to be improved and maintained regarding the quality of service provided by the room attendant staff at The St. Regis Bali Resort. Data collection methods used are observation, questionnaires and literature study. The sample used in this study amounted to 70 respondents with the method of determining the sample, namely accidental sampling. The data was obtained through distributing questionnaires and then tested for validity and reliability. The analytical techniques used in this research are servqual (service quality), and IPA (Importance Performance Analysis). The results of Servqual (service quality) show that the gap of positive servqual scores is more than the gap of negative servqual scores. The servqual results indicate that the quality of room attendant service at The St. Regis Bali Resort as a whole has shown good service. The results of the Importance Performance Analysis show indicators that need to be improved in service quality shown through service attributes/indicators room cleanliness (BL1) and service attributes of room attendant knowledge in understanding a job (J1). Meanwhile, indicators that need to be maintained in service quality are seen through service attributes room attendant appearance (BL2), service attribute condition of room facilities (BL3), service attribute the hospitality of the room attendant in providing services (K2).